The Marine Organisms as Potential Sources of Inhibits ACE on Hypertension Patient - Alma Dyah Perwita; Adam Trojan Alisyahbana; Adinda Ilsa Maulida; Alfia Mawaddah; Ali Ramzi; Legis Ocktaviana Saputri (Jurnal Biologi Tropis, 2023)
Abstract: Hypertension is a condition of chronic high blood pressure in the systemic arteries which is a major risk factor for cardiovascular disease, kidney disorders, and death. There are two types of hypertension, the primary hypertension is thought to be caused by hereditary factors, age, gender, race, and an unhealthy lifestyle. Secondary hypertension is caused by an obvious cause. The prevalence of hypertension in Indonesia is quite high with the highest incidence rate in South Kalimantan (44,1%) and the lowest in Papua (22,2%). The pathophysiology of hypertension involves the enzyme Angiotensin Converting Enzyme (ACE) which plays a role in regulating blood pressure. The process of converting Angiotensinogen to Angiotensin I, then Angiotensin II by ACE can cause vasoconstriction and fluid retention, which contribute to hypertension. The changes in circulation and blood vessel structure have played a role in the risk of hypertension complications, including stroke. The marine organisms such as fish, shellfish, cephalopods, seaweed, and algae contain peptides with antihypertensive, anticoagulant, antithrombotic, and hypercholesterolemic activities. For example, hydrolyzate of the jellyfish, Rhopilema esculentum can inhibit ACE with a high level of effectiveness. The current hypertension treatment often uses synthetic drugs such as ACE inhibitors and Angiotensin Receptor Blockers (ARBs), but these have undesirable side effects. Therefore, bioactive peptides from marine organisms can be an efficient and safe natural alternative. The research on protein hydrolysates from various sources has found ACE inhibitory activity and several peptides such as Trp-Pro-Met-Gly-Phe (WPMGF) and APP, KPLL, and VYPFPGPIPNSLPQNIPP were identified to have strong ACE inhibitory activity. These findings indicate the potential use of bioactive peptides from marine organisms as a natural alternative for the treatment and prevention of hypertension.